Caring for the Domus: On the Evolution of Ecopoetics in the West - Curran, Jesse (The Trumpeter, 2018)
This intimate non-fiction essay traces a lineage of Western ecopoetics and ecological thought to its ancient Roman origins by calling upon David Ferry’s inspired translations of Horace’s Odes, and reading them in light of the philosophical imperatives described by David Orr, Wendell Berry, and other important thinkers, in order to formulate an understanding of how the ongoing environmental crisis is ultimately a crisis of the human spirit. Through creating a linguistic mosaic of Horace’s didactic wisdom enmeshed with current sustainability dialogues and personal experience, the essay lays bare the connections and contingencies between poetry, virtue, sustainability, and ecological existence.